WORK-LIFE BALANCE AND EMPLOYEE PERFORMANCE: REVIEWING GLOBAL PERSPECTIVES - Hidayat, Sidiq; Darmanto, Darmanto; Mu'min, Halek; Dja'wa, Asrianti (Journal Economics Technology And Entrepreneur, 2025)
This systematic literature review integrates global evidence on how work–life balance (WLB) affects employee performance (EP). This synthesizes peer-reviewed articles and policy and organizational reports to surface patterns, contradictions, and gaps. Overall, WLB enhances productivity, engagement, and organizational citizenship via resource conservation, motivation, and supportive leadership–culture alignment, whereas chronic imbalance heightens stress, burnout, absenteeism, and turnover. Effects vary by context: technology enables flexibility yet risks boundary erosion; gendered caregiving loads and institutional scaffolding shape access and impact; and cultural norms around presenteeism condition uptake. High-impact practices combine flexible work, fair workloads, family-supportive supervision, childcare support, and right-to-disconnect norms.